Pengembangan Koreografi Tari Podang Perisai dari Tradisi menjadi Modern di Kuantan Singingi Riau - Irdawati Irdawati; Sukri Sukri (LP2M ISBI Bandung, 2018)
AbstractThis paper explores the development of Podang Perisai dance from a traditional form to a modern one, both textually and contextually. In textual analysis, Podang Perisai dance is related to dance composition including motion, dancers, musical accompaniment, costume, makeup and floor patterns, created by traditional artists who have not had any knowledge about a choreography in its modern meanings. This makes Podang Perisai dance is very simple following requirements at that time. Podang Perisai dance has seven different motions of mulai, sosor, paliang, rantak sabolah, rantak duo bolah, kuak ilalang and lantiang pauah. In its contextual analysis, Podang Perisai dance analyzed related to values of its struggle s in the past to maintain the performance to make it keeps alive following changes in the new era with the advance of technology which can bring tradition to be neglected. The method used in the development of Podang Perisai dance is R&D (Research & Development) method. Furthermore, it also discusses the functions of dance and symbolic meanings contained in those seven different motions.Keywords: development, Podang Perisai dance, modern, tradition. AbstrakTulisan ini merupakan hasil penelitian tentang pengembangantari Podang Perisai dari tradisi menjadi modern, baik secara tekstualmaupunkontekstual. Secara tekstual, tari Podang Perisai berkaitan dengan komposisi tari meliputi gerak, penari, musik pengiring, busana, rias dan pola lantai, yang diciptakan oleh seniman tradisi yang belum mempunyai ilmu tentang koreografi sehingga tari Podang Perisai sangat sederhana sesuai dengan kebutuhan pada waktu itu. tari Podang Perisaimempunyai tujuh ragam gerak yaitu gerak mulai, sosor, paliang, rantak sabolah, rantak duo bolah, kuak ilalang dan lantiang pauah. Dari segi kontekstual, tari Podang Perisai dianalisis mengenai nilai-nilai perjuangan masa lalu yang harus dipertahankan agar tidak hilang begitu saja dengan hadirnya teknologi yang semakin canggih yang membuat nilai-nilai tradisi semakin terabaikan. Metode yang digunakan dalam pengembangan tari Podang Perisaiadalah R&D (Ressearch & Development). Tulisan ini juga membahas tentang fungsi tari dan makna simbolis yang terkandung dalam tujuh ragam gerak.Kata kunci: pengembangan, tari Podang Perisai, modern, tradisi.